Evidence for strong middle Pleistocene earthquakes in the epicentral area of the 6 April 2009 L'Aquila seismic event from sediment paleofluidization and overconsolidation. Issue 7 (24th July 2013) - Storti, F.; Aldega, L.; Balsamo, F.; Corrado, S.; Del Monaco, F.; Di Paolo, L.; Mastalerz, M.; Monaco, P.; Tallini, M.
Abstract [1] Obtaining constraints on maximum earthquake energy from fossil geological evidence has a primary importance for complementing historical information toward the proper mitigation of seismic hazard in a region. In this paper, we describe a newly discovered extensional fault zone in the western L'Aquila basin (Italy), associated with large paleofluidization structures. Paleofluidization‐bearing Calabrian sediments provide evidence for very shallow burial from mineralogical, organic matter thermal maturity, and flat dilatometer test data, whereas density of organic matter shows anomalously high values. We propose that all these pieces of information can be reconciled into a paleoseismological scenario where sediment liquefaction and fluidization in early middle Pleistocene times, as well as dewatering and overconsolidation, were coseismically triggered by strong earthquakes with magnitude approaching or slightly exceeding 7.0.